2003
DOI: 10.21273/hortsci.38.4.607
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Crabgrass Control in Perennial Ryegrass and Creeping Bentgrass Tolerance to Quinclorac

Abstract: Smooth crabgrass [Digitaria ischaemum (Schreber) Schreber ex Muhlenb.] is an invasive weed of cool-season turfgrasses. Previous research has demonstrated that quinclorac is an effective postemergence herbicide for crabgrass control, but performance has been erratic in some regions. Furthermore, quinclorac may elicit objectionable levels of discoloration in creeping bentgrass (Agrostis stolonifera L.). The objectives of this 3-year field study were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 7 publications
3
22
1
Order By: Relevance
“…This response was not observed in Tennessee. Site-to-site variability in quinclorac performance has been reported by other researchers (Dernoeden et al, 2003).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This response was not observed in Tennessee. Site-to-site variability in quinclorac performance has been reported by other researchers (Dernoeden et al, 2003).…”
Section: Resultssupporting
confidence: 69%
“…Similarly, Dernoeden (2001) observed efficacy with mid-postemergence applications (plants with more than three leaves but less than four tillers) of quinclorac in two years of a 3-year study; in the third year, efficacy with quinclorac was not commercially acceptable. In another 3-year study, Dernoeden et al (2003) observed variable control with mid-postemergence applications of quinclorac at 0.84 kgÁha -1 . The researchers suggested that poor performance observed on heavily infested sites might be the result of increased seed reservoirs in soil, rapid plant tillering, and dense mats of smooth crabgrass leaves protecting smaller plants in the canopy from contacting the spray solution.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…), also elicits chlorosis in CBG. The yellowing caused by quinclorac can be partially masked by tank‐mixing the herbicide with chelated iron and nitrogen (3).…”
Section: Introductionmentioning
confidence: 99%
“…Many herbicides, including amicarbazone, bispyribac-sodium; fenoxaprop-p-ethyl, topramezone, and quinclorac are registered on many cool-season turfgrasses, but their use is limited or prohibited on CBG because they cause unacceptable turfgrass injury (Anonymous 2004(Anonymous , 2012a(Anonymous , 2012b(Anonymous , 2013Brosnan and Breeden 2013;Dernoeden et al 2003;Hart et al 2004;Jefferies et al 2013;Johnson 1994;McCullough et al 2010;McDonald et al 2006;Park et al 2002;Reicher et al 2002). For example, fenoxaprop-p-ethyl is widely used to control crabgrass and goosegrass in cool-season turfgrass at 200 g ha À1 (Neal et al 1990).…”
mentioning
confidence: 99%